UJI DAYA HAMBAT EKSTRAK DAUN LIDAH MERTUA (Sansevieria trifasciata laurentii) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Saputra, Kurnia Hadi; Apriliana, Ety; Rodiani, Rodiani; Oktarlina, Rasmi Zakiah (CV. Jasa Sukses Abadi, 2025)
Infectious and communicable diseases remain one of the leading causes of mortality in Indonesia and worldwide. Several pathogenic bacteria can cause infections, one of which is Staphylococcus aureus. This bacterium can lead to a variety of conditions, including mastitis, dermatitis (skin inflammation), respiratory tract infections, impetigo, abscesses, toxic shock syndrome, and food poisoning. With the advent of antibiotics, an increasing number of bacterial strains have developed antibiotic resistance. The primary cause of this resistance is the widespread and irrational use of antibiotics, which allows some bacteria to survive and become resistant. The snake plant (Sansevieria trifasciata laurentii) contains compounds with antibacterial properties, such as tannins, saponins, and flavonoids. This study aimed to investigate the antibacterial activity of snake plant extract against Staphylococcus aureus. The research design used was a laboratory-based observational study. The antibacterial activity of the snake plant leaf extract was tested at concentrations of 20%, 40%, 60%, 80%, and 100% against Staphylococcus aureus using the dilution method to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The results showed that the snake plant extract exhibited antibacterial activity against Staphylococcus aureus at all tested concentrations (20% to 100%). The MIC was observed at a concentration of 20%, while the MBC was found at 40%. These findings confirm that the extract of Sansevieria trifasciata laurentii has inhibitory effects on the growth of Staphylococcus aureus.